Does the design of the NHS Low‐Calorie Diet Programme have fidelity to the programme specification? A documentary review of service parameters and behaviour change content in a type 2 diabetes intervention. Issue 4 (18th December 2022) - Evans, Tamla S.; Dhir, Pooja; Radley, Duncan; Duarte, Cristiana; Keyworth, Chris; Homer, Catherine; Hill, Andy J.; Hawkes, Rhiannon; Matu, Jamie; McKenna, James; Ells, Louisa J.
Abstract: Background: NHS England commissioned four independent service providers to pilot low‐calorie diet programmes to drive weight loss, improve glycaemia and potentially achieve remission of Type 2 Diabetes across 10 localities. Intervention fidelity might contribute to programme success. Previous research has illustrated a drift in fidelity in the design and delivery of other national diabetes programmes. Aims: (1) To describe and compare the programme designs across the four service providers; (2) To assess the fidelity of programme designs to the NHS England service specification. Methods: The NHS England service specification documents and each provider's programme design documents were double‐coded for key intervention content using the Template for Intervention Description and Replication Framework and the Behaviour Change Technique (BCT) Taxonomy. Results: The four providers demonstrated fidelity to most but not all of the service parameters stipulated in the NHS England service specification. Providers included between 74% and 87% of the 23 BCTs identified in the NHS specification. Twelve of these BCTs were included by all four providers; two BCTs were consistently absent. An additional seven to 24 BCTs were included across providers. Conclusions: A loss of fidelity for some service parameters and BCTs was identified across the provider's designs; this may have important consequences for programme delivery and thus programme outcomes. Furthermore, there was a large degree of variation between providers in the presence and dosage of additional BCTs. How these findings relate to the fidelity of programme delivery and variation in programme outcomes and experiences across providers will be examined.